Conceptualizing implementation frameworks from the bottom up: A content analysis of smart city plans - Zhiwei Tang; Krishna Jayakar; Xiaodong Feng; Huiping Zhang; Xiaoyue Peng (International Telecommunications Society (ITS), 2018)
This paper presents a comparative analysis of 52 municipal smart city plans drawn from countries around the world, with the goal of enumerating the specific policies and programs that are included under the general rubric of various "smart city" initiatives. Cluster analysis identified five different models: in addition to an Infrastructure model to which most smart city plans belonged, a Green model, a Utilities model, a Citizen Services model and an E-government model could be identified.
Keywords: 330